Effects of mycorrhizal fungi on symbiotic seed germination of Pecteilis susannae (L.) Rafin (Orchidaceae), a terrestrial orchid in Thailand - Chutima R. (2014)
Symbiotic seed germination of Pecteilis susannae (L.) Rafin was investigated using 11 fungal isolates recovered from roots of four Thai terrestrial orchids (P. susannae, Eulophia spectabilis, Paphiopedilum bellatulum and Spathoglottis affinis). Seed germination and protocorm development were evaluated up to 133 days after sowing. Protocorm development was most advanced, up to stage 5 (elongation of the first leaf), when seeds were cultured with 4 Epulorhiza isolates obtained from roots of P. susannae (CMU-Aug 028, 4.3%, CMU-Aug 007, 4.2%, and CMU-Aug 013, 2.2%) and E. spectabilis (CMU-STE 014, 3.9%). Moreover, stage 4 protocorm development (emergence of the first leaf) occurred with fungal isolates CMU-STE 011, 5.7%, (Epulorhiza sp.) and CMU-AU 212, 4.3%, (Tulasnella sp.) obtained from roots of E. spectabilis and S. affinis respectively. When seed was incubated without fungi (control), development was limited to stage 3 of protocorm development (appearance of promeristem). This is the first report of protocorm stage 5 development in P. susannae using compatible fungal symbionts. Optimization of seed germination and seedling fitness will assist the conservation and propagation of this orchid species and other terrestrial orchids in Thailand. © 2011 Springer Science+Business Media B.V.